Korelasi panjang dan lebar tangan dengan tinggi badan berdasarkan jenis kelamin pada ras mongoloid usia 18-45 tahun di Provinsi (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: This study aimed to determine the correlation and linear regression formula of hand length and breadth with body height. Method: This research was an analytic study with a cross-sectional research design and used the purposive sampling method to take the subject result with a total sample of 236 people (114 men and 122 women) 18-45 age. The study took place from July-December 2019. Results: The result showed a strong correlation between hand length with height and a moderate correlation between handbreadth and height. The highest correlation was on hand length (r=0,89 in male, r= 0,88 in female). Conclusion:  There is a positive relationship between body height, hand length, and handbreadth based on sex in mongoloid race at 18-45 years age in Riau Province.